Theoretical aspects of act in the crime specified in art. 2391 of criminal code «Illegal seizure of soil cover (surface layer) of lands» - Гізімчук, С. В.; Олійник, О. С. (Problems of legality, 2015)
The article is devoted to the investigation of the theoretical aspects of the act as an element of actus reus of a crime under Art. 239-1 of Criminal Code of Ukraine "Illegal seizure of soil cover (surface layer) of lands". The analysis of this element is conducted and, as a result, amendments to existing Criminal Code of Ukraine and land laws are proposed.